The Advantages and functions of social networks for terrorist groups (Case Study: ISIS on Twitter and Facebook) - nematollah fazeli; mohamad soltanifar; Hojjat Ollah Abbasi (مطالعات رسانه‌های نوین, 2018)
In addition to producing and publicating information,Social networks are good platforms for organizational management.The Islamic State (ISIS) plans terrorist operations through social networks, especially Facebook and Twitter.The group advances asks such as the recruitment and organization of forces, planning and implementation of operations, monitoring and control, guidance and leadership, communication and coordination of terrorist operations through telephony in social networks.Twitter and Facebook social networks have goals, benefits and effective performances for the ISIS group .ISIS's goals in these networks include attracting attention, gaining legitimacy and acceptability, identifying, announcing existence and gaining power.Advantages include global audiences, easy access, network power, high speed, horizontal connectivity, inclusive communications, interactive communication, flexible communications and low cost communications.These networks have the informing function, social mobilization and social solidarity for the ISIS terrorist group and advancing its goals on the international scene.This research was conducted to explain the goals, benefits and functions of Twitter and Facebook social networks for the Islamic State's terrorist group with the aim of identifying, controlling and confronting the phenomenon of media terrorism and reducing the damage caused by it.The data of this research have been collected and analyzed through grounded theory and documentary studies.